Charlie Joe Jackson's guide to planet girl - Greenwald, Tom (Square Fish, 2017)
Everyone in Eastport Middle School seems to have a girlfriend or boyfriend, leaving Charlie Joe Jackson the only single guy around. To remedy this unjust situation, Charlie goes to the library and finds a guidebook to love advice. Suddenly, everyone is coming to him for relationship help, especially after he gets his own girl. However, he may have miscalculated the girl he likes, and may get himself into more trouble than he bargained for with the ladies of his class.